Pubertal Changes in Adolescent Girls: A Community Based Cross -Sectional Study - Kollur, Lata R; Pratinidhi, Asha K; Kakade, Satish V (National Journal of Community Medicine, 2013)
Background: Adolescence is a process – a series of varied, rapid and extensive changes as well as period of life. The timing of maturational events varied within healthy children primarily because of genetic factors. Even among healthy youth, there is marked variation in the timing of these maturational changes. Materials and Methods: A cross sectional study was carried out in slum areas adopted under Urban health Training Centre of Department of Community Medicine, KIMSU, Karad. Maharashtra from November 2007 to October 2009, Adolescent girls between 10 to 19 years who were residents of the area adopted for at least five years before inception of study were included. There were 251 adolescent girls of which 200 formed the study group. The study participants were interviewed and examined by house to house survey using pretested structured questionnaire with prior informed consent of parent. Sexual maturity was assessed using Tanner’s Sexual Maturity Score. Analysis was done using SPSS 16 software Results: In present study mean age at commencement of breast, pubic hair, axillary hair and mean age at menarche have been 10.4±0.6, 10.6 ±0.7, 12.2 ±0.7 and13.4 ±1.34years respectively. Breast stage appears earlier than the pubic stage. Time period required for full breast and pubic hair development was 7.3 years and 7.9 years respectively. Conclusion: Timing of sexual maturity indicators could be useful for giving health education regarding hygiene during menstruation and family life education.